Implementasi Pengelolaan Kurikulum dalam Peningkatan Kualitas Pendidikan Berdasarkan Instrumen Akreditasi Satuan Pendidikan (IASP) Tahun 2020 di MTs PERSIS 37 Sumedang - Sahal, Eska Hifdiyah; Nugraha, Mulyawan Safwandy (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2024)
The issues identified in this study are positive, highlighting the unique curriculum of MTs Persis 37 Sumedang, which emphasizes not only general knowledge but also a significant focus on religious education. This approach aims to develop students with a Muslim personality in accordance with Islamic teachings. Consequently, the research seeks to uncover the distinctive elements and information related to the implementation of curriculum management at the institution. The study aims to describe the implementation of curriculum management at MTs Persis 37 Sumedang concerning: 1) curriculum planning, 2) curriculum execution, and 3) curriculum evaluation. Improving educational quality is the primary goal of any educational unit. One effective strategy to achieve this goal is through the implementation of sound curriculum management. This research explores how curriculum management is implemented to enhance educational quality based on the 2020 Education Unit Accreditation Instrument (IASP). Utilizing a literature review method, the study collects up-to-date information on curriculum management in the context of educational accreditation. The findings indicate that effective curriculum management significantly contributes to educational quality, aligning with the standards established in the IASP 2020. This research underscores the crucial role of curriculum management in ensuring that education meets established standards and highlights the need for continuous efforts to optimize curriculum management for sustainable educational quality improvement